Rituximab for desensitization during HLA-mismatched stem cell transplantation in patients with a positive donor-specific anti-HLA antibody - Chang, Ying-Jun; Xu, Lan-Ping; Wang, Yu; Zhang, Xiao-Hui; Chen, Huan; Chen, Yu-Hong; Wang, Feng-Rong; Han, Wei; Sun, Yu-Qian; Yan, Chen-Hua; Tang, Fei-Fei; Huo, Ming-Rui; et al. (Bone marrow transplantation (Basingstoke), 2020)
To define the efficacy of a single dose of 375 mg/m 2 rituximab for DSA-positive patients with 2000 ≤ MFI < 10,000, we enrolled a prospective clinical cohort including patients with positive DSA treated with rituximab ( n = 55, cohort A), a matched-pair cohort including cases with negative DSA ( n = 110, cohort B) and a historical cohort including subjects with 2000 ≤ MFI < 10,000 without receiving any treatment for DSA ( n = 22, cohort C). The incidences of primary poor graft function (PGF) in cohort A and cohort B were 5% and 1% ( P = 0.076), respectively, both of which were lower than that in cohort C (27%, P < 0.001, for all). Rituximab was associated with a reduced incidence of primary PGF (HR 0.200, P = 0.023). The 3-year nonrelapse mortality of patients in cohort A and cohort B were 23% and 24%, respectively, both of which were lower than that in the cohort C (37%), although no statistical significance was observed. These results led to a low 3-year overall survival in patients in the cohort C (58%) compared with those in the cohort A (71%) and the cohort B (73%). We suggest that a single dose of rituximab could be effectively used to prevent the onset of primary PGF. The prospective cohort of this study is registered at http://www.chictr.org.cn/ChiCTR-OPC-15006672 .